Sistem Pendukung Keputusan Pemilihan Kepala Karyawan Produksi Menggunakan Metode Simple Additive Weighting (SAW) - Abednego Erindra Putra; Ikbal Yasin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
CV. Wahyu Putra is one of the companies operating in the agricultural sector that has not utilized information technology in developing its company. This includes the problem of selecting head employees which is still determined subjectively. This problem can be resolved by conducting a performance assessment of each employee to evaluate, motivate and verify in order to improve employee performance. The use of Decision Support Systems (DSS) in human resource management is becoming increasingly important, especially in assessing employees for the selection of chief production employees. Therefore, this research was carried out using the Simple Additive Weighting (SAW) method which has 7 assessment criteria, namely discipline, responsibility, ability, cooperation, thoroughness, leadership and years of service. In the decision making process, testing was carried out on 8 employees in the production department who were alternatives. The results of this research were obtained from calculations using the SAW method starting from determining alternatives, determining criteria and weights, carrying out a normalization matrix, and calculating the final score or ranking results. From the implementation of the SAW method that has been carried out on CV. Wahyu Putra, the recommended candidate for chief employee is alternative A3 with a final value of 0.935. This research provides suggestions on how to determine the head of employees at CV. Putra's revelation, which had previously been carried out subjectively, became objective.